AL AHADEETH AL MUOKOFA AWF BIN MALEK AL ASHGAEE (73 AH) IN SUNNA'S BOOKS (Journal of the College of Basic Education, 2023)
The reasons for my choice of the topic are because; I specialize in the sciences of the Noble Prophet’s Hadith, and my love for studying the hadiths of the Prophet, may God’s prayers and peace be upon him. One of the problems that I faced was the lack of texts in the books of texts, and the importance of the topic. Because it relates to the hadiths of the Prophet, peace be upon him, the second source of legislation, and the objectives of the research; In order to clarify the status of the honorable companions in transmitting what was mentioned about the Prophet, peace be upon him, and I relied in my research on the books of the text of hadith and their explanations, and I recommend researchers to study the hadiths of the Mustafa and clarify them from their sources and pay attention to their scientific graduation; To benefit from it in legal, human and other studies.